Canada : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
KEY ISSUES Economic outlook: The Canadian economy has expanded at a solid pace since 2013, but rebalancing of growth away from household consumption and residential investment remains incomplete, owing mainly to weak business investment. Growth momentum is expected to continue alongside a strengthening U.S. recovery despite substantially lower oil prices. Risks to the outlook are modestly tilted to the downside given sluggish global growth, effects unfolding from sharply lower oil prices, and housing market risks. Key domestic vulnerabilities in housing markets and the household sector remain elevated but contained fro m a financial stability perspective. Policies for balanced and sustained recovery: An appropriate policy mix should help facilitate rebalancing to generate a broader and more durable recovery, reduce domestic vulnerabilities, and further strengthen financial system resilience: -- Macro policies: Monetary policy can remain accommodative for now given that inflation expectations are well-anchored, stronger business investment is still a missing link, risks to an export-led recovery are to the downside, and housing markets are expected to cool as U.S. interest rates rise and with lower oil prices. Fiscal consolidation should proceed in light of longer-term challenges at the provincial level, but federal authorities should consider adopting a neutral stance going forward, using available fiscal resources for targeted measures to support growth. Structural policies to improve productivity in the economy would increasingly need to complement this policy mix. -- Housing sector and financial sector policies: Further macro-prudential policy action may be needed to guard against risks to financial stability if household balance sheet vulnerabilities resume rising. Reforms to limit government exposure to housing markets and encourage appropriate risk retention by the private sector should continue. Improving complex coordination across federal and provincial authorities in supervision and stress- testing of depository institutions and strengthening macro-prudential and crisis management frameworks will reinforce the resilience of Canada's financial system. Policy response to past advice: Since the 2013 Article IV Consultation mission, the authorities have taken some further steps to limit taxpayer exposure to the housing sector and strengthen mortgage insurance underwriting practices. Some work on FSAP recommendations has also started to enhance stress testing, address data gaps, and towards establishing a cooperative capital markets system. The authorities have also intensified their efforts towards addressing interprovincial trade barriers and export diversification.